The Medicinal plants and their economic value in Kakamega Forest Ecosystem: A case study of sustainable land/forest project in Western Kenya - Ojunga, S. O.; Langat , D. K.; Owange, K.; Otuoma, J.; Ayaga, G.; Muskiton, K. C.; Wanyiri, M.; Isack, M. (Journal of Medicinal Herbs and Ethnomedicine, 2023)
Forest Management of ecosystems plays a fundamental role in providing essential goods and services to rural communities. However, there has been a reduction in the natural forest cover due to resource utilization pressure. The pressure on forest resources is catalyzed by the expansion of markets for forest products, agricultural expansion and escalating poverty levels. An upsurge in the number of users of herbal medicine in urban and rural areas has increased the pressure on the forests, while modernization and change in lifestyle have led to the loss of traditional knowledge associated with medicinal plants utilization and conservation. No detailed economic evaluation of medicinal plants has been undertaken and the current illegal, unregulated and unreported exploitation of medicinal plants has led to overexploitation and loss of biodiversity. A better understanding of the abundance, distribution, uses and economic value of medicinal plants is important for the sustainable exploitation and conservation of forests. The study covered four forest blocks of Kakamega, North Nandi, South Nandi and Kibiri to determine plant species diversity, and their distribution in the disturbed and undisturbed areas of the forest; assess knowledge, utilization and economic estimate by willingness to-pay approach of medicinal plants to communities adjacent to the Kakamega Forest. Value chain analysis had been conducted for medicinal plants and forest user groups from Community Forest Association (CFA) had been trained in product development and access market were used in the study. Experimental Plot techniques were also used to gather ecological data on the frequency, density, diversity and distribution of the plants, whereas key informant interviews, focus group discussions and household interviews were utilized to gather information on ethnobotanical knowledge and household socioeconomic data. Thirty-two key species of medicinal plants were identified and used by local people around the Kakamega forest ecosystem. Forty-seven percent (47%) of these were trees, thirty four percent (34%) were shrubs, sixteen percent (16%) were herbs and climbers three percent (3%). Seventy percent (70%) of the medicinal plants were within the forest and thirty percent (30%) were outside the forest. The three most dominant families were Euphorbiaceae, Piperaceae and Fabaceae with leaves as the most common plant part used constituting 31 % (n=26) of the preparations, followed by roots with 20% (n=17),bark with 14% (n=14), fruits with 11 % (n=9), seeds having 11% (n=9), flowers 2% (n=2) and sap 2 % (n=3). The economic benefits generated from the medicinal plants within the forest ecosystem services in the Kakamega-Nandi landscape in terms of direct use value was about KES 601,918,256 (≈USD 5.19 million) per year, while indirect use value was KES 317,288,046 (≈USD 2.74 million) per year. Indigenous knowledge of the medicinal uses of the plants, their commercial aspects and distribution trends in the forest provision of wide scope for understanding relevant market systems may be tapped for decision support in rural health service planning, policy formulation for conserving the forest, tracking and mitigation of climate change impacts.